Unsur Naratif Pada Permainan Seluler “Selera Nusantara – Episode: Nasi Goreng” - Setiawan, Fredy Nugroho (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2024)
“Selera Nusantara” is a mobile simulation game from Indonesia. The game not only offers cooking simulation challenges for the players but also provides information about the main characters who appear between game levels. The existence of story elements in the permainan seluler is the focus of this research. In this case, we chose “Selera Nusantara – Episode: Nasi Goreng” as the object of study. This research is about how the narrative aspect in the permainan seluler "Selera Nusantara – Episode: Nasi Goreng" is built. The arguments proposed by Egenfeldt-Nielsen, Smith, and Tosca in their book, Understanding Video Games (2020), are used as the theoretical framework of this research, especially the discussion about narrative. The results of this research show that the narrative aspect in "Selera Nusantara - Episode: Nasi Goreng" is constructed through a series of cutscenes which, if separated from the game mechanics and put together sequentially from level to level of the game, form a progressive plot identical with stories in short stories, novels, or film. Although integrated in the game, the plot does not affect the simulation game session. However, to be able to understand the complete series of stories that form the context of the game world (gamespace), players must go through each stage of the level. Thus, it can be concluded that the story fragments which become the background of "Selera Nusantara – Episode: Nasi Goreng" provide a narrative to the game, which makes it a form of ergodic literature.